PETANDA KEBAHAYAAN (RISIKO) PENYAKIT JANTUNG KORONER TERKAIT LDL - Adi Priyana . (Indonesian Association of Clinical Pathologist and Medical laboratory, 2008)
Atherosclerosis is the most common cause of coronary heart disease (CHD), and it is still the primary cause of death in Indonesia and most industrialized countries. The conventional risk factor for atherosclerosis and CHD are diabetes mellitus, hypertension, dyslipidemiaand smoking. On the other hand, Lp (a), homocystein and small dense LDL (sd-LDL) have been considered as novel risk factors for CHDLow of high density lipoprotein (HDL), high of low density cholesterol (LDL-c) and high homocystein as part of dyslipidemia, has beenconsidered as independent risk factor for CHD.The principal objective of the present study was to compare between HDL-c, Lp (a), andsd-LDL and homocystein as a risk marker of CHD. The study subject were divided into two groups, risk group consist of 94 subjects whohad > 2 CHD risk factors and control group recruited 49 subject who had no CHD risk factors. Both groups had fasted for 10-12 hourbefore their sera were collected. The sera were examined for HDL-c, Lp (a), sd-LDL and homocystein. Four alternative multivariate modelwere compared: sd-LDL, sd-LDL + HDL-c, sd-LDL, HDL-c + Lp (a) and sd-LDL, HDL-c + sd-LDL + Lp (a) + homocystein. Result of thistudy showed that the sd-LDL had the most significant and accurate as risk marker for CHD. Lp (a), HDL-c and homocystein were lessaccurate if used as risk marker for CHD compare with sd-LDL. Small dense LDL is an accurate risk marker for CHD. Further study musbe done using larger sample size of CHD subjects with similar age between risk and control groups.